2021
DOI: 10.1097/sla.0000000000004997
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes in Endoscopic and Operative Transgastric Pancreatic Debridement

Abstract: Objectives: Select patients with anatomically favorable walled off pancreatic necrosis may be treated by endoscopic (Endo-TGD) or operative (OR-TGD) transgastric debridement (TGD). We compared our experience with these 2 approaches. Summary Background Data: Select necrotizing pancreatitis (NP) patients are suitable for TGD which may be accomplished endoscopically or surgically. Limited experience exists contrasting these techniques exists. Methods: Patients undergoing Endo-TGD and OR-TGD at a single, highvolum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 33 publications
(88 reference statements)
0
8
0
1
Order By: Relevance
“…The anatomy of the patient's necrosis and their physiology determine the appropriate techniques for the step-up approach. The pros and cons of different techniques are described in the Table, 11,[13][14][15][16][17][18][19][20][21][22] and a general treatment algorithm for their use is depicted in Figure 2. 16 There is no overarching evidence demonstrating that one technique is preferred over another in the step-up armamentarium, but instead, the sequence of interventions is guided by the particular circumstance of each individual.…”
Section: Overview Of the Step-up Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…The anatomy of the patient's necrosis and their physiology determine the appropriate techniques for the step-up approach. The pros and cons of different techniques are described in the Table, 11,[13][14][15][16][17][18][19][20][21][22] and a general treatment algorithm for their use is depicted in Figure 2. 16 There is no overarching evidence demonstrating that one technique is preferred over another in the step-up armamentarium, but instead, the sequence of interventions is guided by the particular circumstance of each individual.…”
Section: Overview Of the Step-up Approachmentioning
confidence: 99%
“…Compared with ETN, STN provides the opportunity to perform extensive debridement at the index operation and maintains the advantage of internal drainage of the necrosis cavity, while often avoiding the multiple procedures typically required with less invasive techniques. 18,22 For patients with disconnected pancreatic tail segments, the surgical anastomosis to the necrosis cavity may provide more durable internal drainage than stent- A, An intercostal, transperitoneal drainage route that accesses the end of the walled-off necrosis and would allow debridement via sinus tract endoscopy. Accessing the end of the cavity as opposed to the middle allows access to the entire cavity.…”
Section: Surgical Transgastric Necrosectomymentioning
confidence: 99%
“…В заключение следует отметить, что чрескожное и трансмуральное эндоскопическое дренирование относятся к наиболее распространенным и зффективным методам первой линии миниинвазивного лечения пациентов с отграниченным панкреонекрозом. Эндоскопическое трансмуральное дренирование может быть более предпочтительной процедурой, поскольку позволяет избежать риска образования наружных панкреатических свищей [3,8,60].…”
Section: список литературыunclassified
“…5,6,[9][10][11][12] As previous clinical studies mainly focused on WON ranging from 8 to 15 cm in diameter, data about the efficacy of endoscopic and video-assisted retroperitoneal treatment of WON larger than 15 cm are scarce. 8,10,[13][14][15][16][17][18][19][20] A recent study clearly demonstrated that the localization and size of extra pancreatic necrosis are associated with clinical outcomes, including mortality, LOS, and intensive care unit (ICU) stay in patients with acute necrotizing pancreatitis. 21 Thus, there is an unmet need for data to assess the efficacy and safety of a minimally invasive treatment approach for large WON, especially if large WON can be managed without open necrosectomy.…”
Section: Introductionmentioning
confidence: 99%
“…As previous clinical studies mainly focused on WON ranging from 8 to 15 cm in diameter, data about the efficacy of endoscopic and video‐assisted retroperitoneal treatment of WON larger than 15 cm are scarce 8,10,13–20 . A recent study clearly demonstrated that the localization and size of extra pancreatic necrosis are associated with clinical outcomes, including mortality, LOS, and intensive care unit (ICU) stay in patients with acute necrotizing pancreatitis 21 .…”
Section: Introductionmentioning
confidence: 99%